Harnessing Diversity through Visionary Leadership: Empowering Women and Communities in Awach SACCOS, Ethiopia - Erensa, Zerihun Sheleme (Cooperativismo & Desarrollo, 2025)
This paper examines how visionary leadership and strategic inclusion of women have transformed Awach Saving and Credit Cooperative Society (SACCOS) into a thriving financial institution in Ethiopia. It highlights the transformative impact of visionary governance, focusing on the leadership that has steered Awach SACCOS towards addressing economic disparities and empowering marginalized groups, particularly women. Drawing on plans, reports, and relevant literature, the study provides a comprehensive analysis of Awach SACCOS’s transformative journey. Guided by a visionary approach inspired by successful savings and credit models, the leadership of Awach SACCOS established a community-centered financial institution that prioritizes inclusivity. The cooperative has introduced tailored financial products for women and youths, fostering economic growth and financial independence. Awach SACCOS has seen substantial growth, with membership rising to 143,095 by February 2024, 38% of whom are women. Women benefit from customized loan products, lower interest rates, and opportunities for entrepreneurial ventures and leadership. The paper underscores Awach SACCOS's achievements in promoting gender equality and economic empowerment. Awach SACCOS has enhanced financial access for women and youths, contributing significantly to Ethiopia's socio-economic development. This case exemplifies how cooperative governance and diversity-focused visionaries can drive impactful community transformation.
Keywords: Women empowerment; visionary leadership; community-centered and financial independence